Influence of Additives on Phosphate-Bounded Fire-Resistant Materials - Yesiltas, Ersin; Genc, Yasin; Yeprem, H. Aygul (CARL HANSER VERLAG, 2011)
Influence of Additives on Phosphate-Bounded Fire-Resistant Materials. This work aims to investigate how phosphoric acid, barite and boric acid addition effects properties of phosphate bonded high alumina refractory bricks. In this study physical and analytical tests were made for phosphoric acid, phosphoric acid + barium sulfate (barite) and phosphoric acid + barium sulfate + boric acid added high alumina bricks which were tempered at 825 degrees C or fired at 1350 degrees C. In addition to these tests molten aluminum penetration in these high-alumina alumina-silicate refractories were investigated. Molten aluminum alloyed with 5 wt.-% magnesium to form an aggressive environment and then high alumina bricks tested for aluminium penetration according to norm of DIN 51069 Tiegel (cup) test. A high alumina bauxite based refractory brick tested for penetration test to create a reference brick.
Keywords: Materials Science